Compact and Broadband 300 GHz Three-Element on-chip Patch Antenna - Pfahler, Tim; Vossiek, Martin; Schür, Jan (IEEE Radio and Wireless Symposium, RWS, 2023)
This paper presents a 300 GHz three-element on-chip patch antenna with lateral coupled parasitic patch elements. The achieved matching bandwidth is 26 GHz. The key advantage of the proposed design is the resulting broadband characteristic with simultaneous lateral geometric compactness of the antenna to fit into an array with λ0/2-spacing at the target frequency. Due to this lateral compactness and the resulting greater gap between adjacent array elements the mutual coupling can be minimized. A realized gain larger than 0 dBi is achieved over a bandwidth of 21 GHz with a simulated peak antenna gain of 1.7 dBi at 295 GHz. Moreover, the beam pattern is frequency independent without a pattern-tilt/distortion over the considered frequency bandwidth which makes the antenna particularly appropriate for beam steering on MIMO antenna-array applications in broadband Sub-THz communication and high-resolution radar sensing.
Created from Fastlane, Scopus look-up
Keywords: antennas; array; millimeter wave integrated circuits; MIMO; on-chip; terahertz